“Death may suck, but it’s better than the emergency room”, Lived experiences of healthcare avoidance and systemic harm among people experiencing homelessness: A meta-synthesis - Tracey McElwee; Trey Myrick; Tara V. DeJohn; Sheralyn Beck; Mia Dancy; Leah Goldsholl; Samantha Greer; Aubry Hutton; Frida Mateo-Rodriguez; Rachel Norwood; Stephanie Davis-Clegg; Melissa Sanders; Kaylin Walker; Charlotte Watson (Science Center Group, 2026)
Background: People experiencing homelessness face persistent structural and interpersonal barriers to healthcare that contribute to delayed care, avoidance, and preventable harm. While disparities are well documented, less is known about how repeated healthcare encounters shape engagement over time. Purpose: This qualitative interpretive meta-synthesis examined healthcare access and avoidance among people experiencing homelessness and service providers to identify shared barriers influencing system navigation and care delivery. Methods: An adapted qualitative interpretive meta-synthesis design was employed. Systematic searches were conducted across eight academic databases between January and April 2025. Peer-reviewed qualitative studies focused on adult homelessness and healthcare access were included. Verbatim participant quotations were extracted and analyzed using line-by-line coding, constant comparative analysis, and team-based synthesis. Results: Fifteen qualitative studies met inclusion criteria, representing 334 unhoused individuals and 72 service providers. Six interconnected themes emerged: systemic stigma in healthcare settings; financial inaccessibility and cost-related avoidance; fear-based avoidance of healthcare systems; barriers due to bureaucracy and lack of information; dehumanization and the emotional toll of healthcare encounters; and marginalized mental health needs within fragmented healthcare systems. Findings suggest healthcare avoidance often reflects rational responses to cumulative systemic harm rather than disengagement. Conclusions: Healthcare exclusion among people experiencing homelessness is driven by intersecting structural, clinical, and relational failures identified by both service users and providers. Trauma-informed, equity-oriented, and person-centered approaches are essential to improving access, trust, and continuity of care in community nursing and primary care settings.